Bude zítřek posthumanitní? (Czech Journal of International Relations, 2000)
Intellectual quarrels, conducted on a worldwide scale, are in no way normal. One of these was triggered at the beginning of 1989 by an article by Francis Fukuyama on the “end of history”. Today, ten years later, this American thinker comes forward with a new theory. Liberalism has managed to triumph and that is why only the kind of history, decided by the human natural state, ends. Thanks to biotechnologies, we find ourselves on the threshold of a fundamental change of the human essence. It is, therefore, more accurate to talk not of the end of history, but of the appearance of a new era which can be called post-humanitarian. Yet Fukuyama proceeds from the view that nothing which has occurred in international politics and in the world economy over the past ten years refutes his claim that liberal democracy and a market economy constitute the only viable way out for modem society. In addition to the evaluating introduction, Zdeněk Müller’s contribution puts before the reader an excerpt of Fukuyama’s essay “Second Thoughts: The last man in a bottle”, featured in the periodical The National Interest. Fukuyama’s mentioned essay then deals at length with the following problems: 1) science as a fundamental driving force, 2) the model called the Washington consensus, 3) questions of nationalism, 4) the contemporary financial crisis, 5) the problem, called the end of the end of history, 6) globalization as an irreversible phenomenon in the history of human civilization, 7) democratic syllogism. 8) the “ultimate border” of human history, 9) the role of recognition and respect in the advancement of mankind, 10) the era of biological discoveries, 11) the impact of chemical discoveries in influencing the personality of the human being, 12) androgyny, 13) information technologies.On the basis of an analysis of the mentioned problems, the author reaches the conclusion that the unlimited possibilities of modem science allow the present to anticipate that after two or three generations we shall have at our disposal the kind of knowledge and technologies which will enable us to be successful in areas where social engineers have failed. It is in this stage that the history of humanity will definitely come to a close since humanity itself will eradicate the human being as a natural being. That is when a new post-humanitarian history will be able to commence.